Retinoids in the visual cycle: role of the retinal G protein-coupled receptor - Choi, Elliot H. (J Lipid Res, 2021)
Driven by the energy of a photon, the visual pigments in rod and cone photoreceptor cells isomerize 11-cis-retinal to the all-trans configuration. This photochemical reaction initiates the signal transduction pathway that eventually leads to the transmission of a visual signal to the brain and leaves the opsins insensitive to further light stimulation. For the eye to restore light sensitivity, opsins require recharging with 11-cis-retinal. This trans-cis back conversion is achieved through a series of enzymatic reactions composing the retinoid (visual) cycle. Although it is evident that the classical retinoid cycle is critical for vision, the existence of an adjunct pathway for 11-cis-retinal regeneration has been debated for many years. Retinal pigment epithelium (RPE)-retinal G protein-coupled receptor (RGR) has been identified previously as a mammalian retinaldehyde photoisomerase homologous to retinochrome found in invertebrates. Using pharmacological, genetic, and biochemical approaches, researchers have now established the physiological relevance of the RGR in 11-cis-retinal regeneration. The photoisomerase activity of RGR in the RPE and Müller glia explains how the eye can remain responsive in daylight. In this review, we will focus on retinoid metabolism in the eye and visual chromophore regeneration mediated by RGR.